O conceito de angústia em Kierkegaard e Heidegger: consonâncias e dissensões. - Massarollo Júnior, Leosir Santin (2020)
The research had as its theme the concept of anxiety in the thinking of two contemporary philosophers, Kierkegaard and Heidegger. The objective was to determine how much the thinkers understand this object; secondly, it intended a comparative study of these understandings, seeking to establish differences and similarities between them. Based on two of the works in which the focused theme appears, we worked primarily with The concept of angst, the work of the Danish thinker, and Being and Time, from the German. The task facing these works was to reconstruct the concept of angst in each of these, the way that this notion, in the end, could be expressed in its most insinuating features. The reconstruction was designed to consider hermeneutically the aims, positions and previous conceptualities of the two philosophers. Thus, in the case of Kierkegaard, his psycho-dogmatic methodology, in other words, the biblical contexts that serve as a scenario for the illustration of ideas, were discussed: "Freedom of choice", "hereditary sin", "paradigmatic Adam", "qualitative leap", "possibility", "individual", "guilt" and, properly speaking, "angst". In Heidegger’s case, from a phenomenological-existential approach, notions such as “being-there”, “being-in-the-world”, “decadence”, “impersonality”, “fundamental affective tones”, “pathetic crisis” and “property” were on the agenda. In both cases, we tried to focus on the concept in question in view of the scenario of existence. In the third chapter, it was established, by means of comparison between the two positions approached, as the ideas of “angst”, “possibility”, “authenticity”, “freedom”, “nothing” and “guilt” are evident. At the end of our movement of exposure and analysis, we believe we can conclude that there are more points of "consonance" than of "dissonance" between the two thinkers, and the fact that both start from existence and define their discussions in this field is, in part, determinant of such balance. Another result that points out similarities between the thinkers understandings live in the fact that the anxiety, in both cases, is somehow related to the idea of "self", of individuation. Among the dissentions, we identified that the approaches to the object studied are diverse, as is the fact that the redemption of the decadent existence by angst, in the case of Heidegger, do not go through the idea of God, so valuable to the Kierkegaardian thinking.